2016
DOI: 10.1021/acs.joc.5b02844
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Bioinformatic Assignment of Methyl-Bearing Stereocenters, Total Synthesis, and an Additional Molecular Target of Ajudazol B

Abstract: Full details on the evaluation and application of an easily feasible and generally useful method for configurational assignments of isolated methyl-bearing stereocenters are reported. The analytical tool relies on a bioinformatic gene cluster analysis and utilizes a predictive enoylreductase alignment, and its feasibility was demonstrated by the full stereochemical determination of the ajudazols, highly potent inhibitors of the mitochondrial respiratory chain. Furthermore, a full account of our strategies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 223 publications
0
15
0
Order By: Relevance
“…The stereospecificity motifs have been used to predict accurately the stereochemistry of many polyketides (Tietz and Mitchell, 2015;Essig et al, 2016). It is now known that the stereostructure of filipin agrees with that inferred from the sequence of the polyketide synthase (Gao et al, 2014;Ikeda et al, 2014).…”
Section: Polyene Biosynthesis and Polyketide Stereochemistrymentioning
confidence: 94%
“…The stereospecificity motifs have been used to predict accurately the stereochemistry of many polyketides (Tietz and Mitchell, 2015;Essig et al, 2016). It is now known that the stereostructure of filipin agrees with that inferred from the sequence of the polyketide synthase (Gao et al, 2014;Ikeda et al, 2014).…”
Section: Polyene Biosynthesis and Polyketide Stereochemistrymentioning
confidence: 94%
“…NaOH solution (143 mL, 215 mmol) was then cautiously added, and the resulting mixture was stirred at rt for 18 h. The layers were separated, and the aqueous phase was extracted with CH 2 Cl 2 (3 × 250 mL). The aqueous layer was then cooled down to 0°C, and acidified to pH ≤ 2, by the slow addition of 3…”
Section: (S)-tert-butyl(2-methylpent-4-enyloxy)diphenylsilanementioning
confidence: 99%
“…[2] Ajudazol B was also shown to be an effective inhibitor of 5-lipoxygenase (5-LO), which is a molecular target for the treatment of asthma and allergic rhinitis. [3] The exciting combination of unique structural features and their interesting antifungal activity has made the ajudazols attractive targets. Rizzacasa [4] and Taylor [5] have published elegant approaches towards the total synthesis of the ajudazols; with the only completed total synthesis to date reported by Menche.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the mild reaction conditions and ease of handling of organoboron reagents [ 13 17 ] have propelled the growth of the SM cross coupling. A synergistic combination of these two elegant methods (i.e., SM coupling and metathesis) [ 18 ] was found to increase the synthetic efficiency of complex targets (e.g., macrocycles [ 19 22 ], oligomers [ 23 24 ], polycyclic ethers [ 25 ], heterocycles [ 26 ], nonbenzenoid aromatics [ 27 ], and spirocycles [ 28 29 ]) by decreasing the number of steps. Different metathesis catalysts used in this study are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%